2006
DOI: 10.1380/ejssnt.2006.504
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of heavy metals by exhausted coffee grounds as a potential treatment method for waste waters

Abstract: The adsorption of the heavy metal ions Cu 2+ , Zn 2+ , Cd 2+ and Pb 2+ from aqueous solution by used coffee grounds has been investigated as a potential low-cost treatment method for heavy metal-containing waste waters that is based on a readily available natural by-product. The results show that metal ion adsorption is efficient over a fairly wide pH range and adsorbed metals are reversibly leached from the exhausted coffee by dilute acid without significant loss of the adsorptive capacity for subsequent re-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 5 publications
2
21
0
3
Order By: Relevance
“…et al [35] and similar to the value reported by Utomo, H.D. et al [18]. The theoretical values of adsorption reported in the literature for alginate beads vary.…”
Section: Analysis Of Adsorption Isothermssupporting
confidence: 83%
See 1 more Smart Citation
“…et al [35] and similar to the value reported by Utomo, H.D. et al [18]. The theoretical values of adsorption reported in the literature for alginate beads vary.…”
Section: Analysis Of Adsorption Isothermssupporting
confidence: 83%
“…After drying, SCGs were sieved through a #35 ASTM sieve (500 µm). Previous experiments in metal removal, where the employed coffee was only washed with deionized water, showed that this adsorbent continued to release soluble coffee material on subsequent exposure to aqueous solution [18]. Therefore, the SCGs were pretreated with 0.1 M NaOH (Fisher Chemical, Fair Lawn, NJ, USA) to remove the soluble materials as described in Dávila-Guzmán, N.E.…”
Section: Spent Coffee Grounds (Scgs)mentioning
confidence: 99%
“…Using potentiometric titration the acid base chemistry and stoichiometry of H + ion were studied for tea leaves and coffee grounds. Hence the study concluded that tea and coffee residues can be used to remove trace metal ions from water [105]. Table 1 shows the specific metal adsorption capacity of various agricultural wastes where several authors evaluated the adsorption efficiency for various heavy metals by using different isotherm models which shows the interaction pattern between the adsorbate and adsorbent.…”
Section: The Green Technology: Usage Of Effective Bioadsorbentsmentioning
confidence: 99%
“…Hal ini disebabkan karena pada pH netral ion-ion logam dapat mengalami reaksi hidrolisis dalam larutan sehingga ia tidak stabil dalam bentuk ion logam semula dan menyebabkan kemampuan sekam padi untuk menyerapnya menurun. Sedangkan pada pH basa, ion-ion logam dapat membentuk endapan hidroksida sehingga efisiensi penyerapannya sukar untuk ditentukan (Refilda et al, 2001;Utomo et al, 2006).…”
Section: Hasil Dan Pembahasanunclassified